WASTE MANAGEMENT IN RESIDENTIAL AREAS BORDERING BANDA ACEH BASED ON THE CONCEPT OF ḤIFZ AL-BĪ’AH: A Case Study of The Aceh Besar Regency Environmental Agency - Al Janwir, Haris; Abdul Razaq; Gamal Achyar (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
This study analyzes the waste management issues in residential border areas between Aceh Besar District and Banda Aceh City. The research arises from the persistence of complex environmental problems, marked by illegal waste accumulation, limited facilities, weak cross-regional coordination, and low public awareness. Three aspects are examined: the analysis of waste management policies, the synergy between government and community, and the perspective of ḥifẓ al-bī’ah (environmental protection). The research employs a qualitative approach with a sociological-empirical legal method. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that waste management policies have not been implemented optimally due to limited transportation fleets and facilities, weak community education, and ineffective cross-regional coordination. The existing synergy between government and community remains sporadic and unsustainable. From the perspective of ḥifẓ al-bī’ah, waste management in residential border areas of Aceh Besar District and Banda Aceh City has not fully realized environmental protection. Therefore, strengthening policies, enhancing public awareness, and fostering cross-sectoral collaboration between the two regions are urgently required.